2015
DOI: 10.1615/atomizspr.2015010623
|View full text |Cite
|
Sign up to set email alerts
|

A Spherical Volume Interaction DDM Approach for Diesel Spray Modeling

Abstract: This work presents an implementation and evaluation of an alternative approach for describing exchange of mass, momentum and energy in Diesel spray CFD simulations using Discrete Droplet Modeling (DDM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…With reference to the standard k-ε turbulence model, it was observed that the value of the C ε1 constant heavily influences the outcome of spray simulations. For diesel sprays, which are predominantly characterized by a round jet shape of the plumes, a value greater than 1.44 allowed for more accurate results [38] by mitigating the tendency of the models to overpredict the round jets spreading rate [39]. On the other hand, the jets of GDI sprays are closer and they are thus subjected to a different flow field.…”
Section: Standard Ecn Condition: Spray Penetrationmentioning
confidence: 99%
“…With reference to the standard k-ε turbulence model, it was observed that the value of the C ε1 constant heavily influences the outcome of spray simulations. For diesel sprays, which are predominantly characterized by a round jet shape of the plumes, a value greater than 1.44 allowed for more accurate results [38] by mitigating the tendency of the models to overpredict the round jets spreading rate [39]. On the other hand, the jets of GDI sprays are closer and they are thus subjected to a different flow field.…”
Section: Standard Ecn Condition: Spray Penetrationmentioning
confidence: 99%
“…Pope (Pope, 1978) stated in his work, that by using the higher value of C ε1 may yield better results as a round jet correction. For a diesel spray, which is approximated as round jets, when an increase in C ε1 values resulted in better agreement with the experimental data (Torelli et al, 2015). It is important to note here, C ε1 1.44 seems sufficient to get reasonable agreement for liquid and vapor penetrations.…”
Section: Model Validation With Ecn Datamentioning
confidence: 73%
“…It is noted that the KH-RT model is meant to describe the mechanical and aerodynamic instabilities of liquid jets, and, in principle, cannot represent the flash-boiling-induced atomization mechanism. Nevertheless, this breakup model (as well as the other spray submodels mentioned above) is commonly and widely used to model spray breakup in ICE applications under many conditions, [39][40][41][42] often without recognizing its applicability limits. Hence, one of the goals of this study is to assess the KH-RT model performance when dealing with flash boiling sprays.…”
Section: Modeling Approachmentioning
confidence: 99%